'We would like this place to be a town': The benefits and challenges of rural development near protected areas. (December 2021) - Strong, Michael; Silva, Julie A.
Highlights: Rural dwellings constructed using finished materials, including glass windows and tiled roofing, are rapidly proliferating. Residents express a shifting preference for upgraded dwellings over large cattle herds. Exposure to upgraded dwellings corresponds with more positive assessments of community-wide development. Aspirations for upgraded dwellings expand as people witness successful upgrading strategies. Abstract: The degree to which African small town development poses a challenge to conservation near protected areas remains understudied. Low levels of economic development limit the ability to investigate and theorize how rural populations alter the built environment as incomes rise. This study examined the spatial and temporal dynamics of dwelling construction in two Mozambican villages located near Limpopo National Park where rhino poaching has financed rapid rural development. We analyzed 495 photographs of the built environment and 110 semi-structured interviews occurring over a six-year period (2009–2015) corresponding with increased rhino poaching. We find a rapid and exponential increase in dwellings rebuilt or renovated exclusively with finished construction materials, a process we refer to as upgrading. Exposure to upgraded dwellings corresponds with positive assessments of community-wide development, even for individuals not living in these dwellings. Residents of neighborhoods with the least upgrading were most likely to discuss low quality dwellings as diminishing human dignity. Taken together, these findings suggest growing acceptance of illegal activity as a development strategy in rural communities.